2007
DOI: 10.1073/pnas.0709311104
|View full text |Cite
|
Sign up to set email alerts
|

A structural basis for enhancement of long-term associative memory in single dendritic spines regulated by PKC

Abstract: Using both scanning confocal and electron microscopic morphometric measurements, we analyzed single dendritic spines of CA1 pyramidal cells in the hippocampi of water maze-trained rats vs. controls. Two days after completion of all training, we observed a memory-specific increase in the number of mushroom spines-all of which make synaptic contacts-but not in the numbers of filopodia or stubby or thin spines, as quantified with double-blind protocols in both scanning confocal and electron microscopic images. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 24 publications
(26 reference statements)
7
111
0
4
Order By: Relevance
“…Our present EM data show that the bryostatin-1 treatment prevented the ischemic loss of the preexisting ultra-structures for long-term associative memory, that is, perforated PSD mush- room spines that form synapses with an axonal bouton containing a high volume of presynaptic vesicles (10). Double-blind electron microscopy was used to investigate the effects of ischemia/hypoxia and/or bryostatin-1 on the number of mushroom spines and the number of axonal boutons with high concentration of presynaptic vesicles (n ϭ 48-62 electron micrographs; see Fig.…”
Section: Bryostatin-1 Induces Synaptogenesis and Prevents Global Cerementioning
confidence: 60%
See 2 more Smart Citations
“…Our present EM data show that the bryostatin-1 treatment prevented the ischemic loss of the preexisting ultra-structures for long-term associative memory, that is, perforated PSD mush- room spines that form synapses with an axonal bouton containing a high volume of presynaptic vesicles (10). Double-blind electron microscopy was used to investigate the effects of ischemia/hypoxia and/or bryostatin-1 on the number of mushroom spines and the number of axonal boutons with high concentration of presynaptic vesicles (n ϭ 48-62 electron micrographs; see Fig.…”
Section: Bryostatin-1 Induces Synaptogenesis and Prevents Global Cerementioning
confidence: 60%
“…Data were analyzed by double-blind quantification (unknown treatment and animal subject) from electron micrographs (10 m ϫ 10 m). Morphology of mushroom-shape dendritic spines, presynaptic axonal boutons, and synapses were quantitatively analyzed according to Hongpaisan and Alkon (10). The criteria of mushroom spines are dendritic spines with (cross-sectionally visualized) diameter Ͼ600 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental cerebral ischemia is usually induced focally through, for example, occlusion of the middle cerebral artery, or globally, through permanent occlusion of two arteries (bilateral vertebral arteries in a 4-vessel occlusion model or carotid arteries) associated with a controlled period of occlusion of the other two arteries (bilateral carotid arteries), hypotension, or hypoxia (6, 15). In young adult animals, the combined procedure is essential to induce ischemic pathophysiologic consequences (6, 16-19).Using confocal and electron microscopy, the potent PKC activator bryostatin was recently shown to enhance precisely those structural and ultrastructural changes in hippocampal synapses specifically affecting rat spatial maze learning and memory (20). Based on that study and other studies (21-24), as well as on previous observations of ischemia/hypoxia-induced damage to CA1 hippocampal neurons (14), we investigated the possibility that bryostatin also may reduce or prevent the aforementioned neuronal and synaptic damage in the postischemic brain.…”
mentioning
confidence: 99%
“…Bryostatin-1, which crosses the blood-brain barrier when administered peripherally (28), produces a relatively selective activation of the PKC isozyme, which is neuroprotective (29-31) and has a lower median effective dose than PKC␦ for bryostatin-1 in its translocation (thus activation), whereas PKC␦ is most likely involved in ischemic injury during ischemia-reperfusion (32-34). We recently showed that PKC activation with bryostatin-1 enhanced exactly those synaptogenesis, presynaptic/postsynaptic ultrastructural specialization, and protein synthesis functions involved in rat maze learning and memory (20,35). PKC activation has at least two actions that may be relevant to PKC signal processing: activation of PKC isozymes at low concentrations and protection of active, membrane-bound PKC from degradation under stress.…”
mentioning
confidence: 99%